The Influence of Motivation on Employee Work Productivity at PT. Telkom North Jakarta - Iksan, La Ode; Fauzobihi, Fauzobihi; Rahman, Erik (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this research is to determine the motivation for employee work productivity at PT. Telkom North Jakarta. This research uses quantitative descriptive methods with data collection techniques through distributing questionnaires and library data. In this research, the saturated sampling method used was 68 employees of PT. Telkom North Jakarta, using simple linear regression data analysis techniques. The results of this research show that there is an influence between motivation on the work productivity of PT employees. Telkom North Jakarta and work discipline have a strong positive influence and have an influence contribution of 46.6% on employee work productivity variables. It is hoped that the results of this research will contribute to further research.